1982
DOI: 10.2307/1240636
|View full text |Cite
|
Sign up to set email alerts
|

Migration to the United States and Mexican Rural Development: A Case Study

Abstract: An analysis of the impact of migration to the United States on the sending community and on the labor market in the receiving country is presented based on a case study of Las Animas, Mexico. "As the community becomes increasingly involved in migration, tendencies can be identified regarding changing migration patterns, class differentiation among villagers, impact of migration on village economy, and the changing role of Mexican workers in California labor markets. Results indicate the importance of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 8 publications
1
30
0
3
Order By: Relevance
“…These findings, based on data from 119 communities in 21 states, generalize similar patterns observed by Cohen (2002) in 13 communities in Oaxaca, Jones (1995) in 4 communities in Zacatecas, Mines and de Janvry (1982) in a community in Zacatecas, and finally, Mines and Massey (1985) in two communities in Zacatecas and Michoacán.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These findings, based on data from 119 communities in 21 states, generalize similar patterns observed by Cohen (2002) in 13 communities in Oaxaca, Jones (1995) in 4 communities in Zacatecas, Mines and de Janvry (1982) in a community in Zacatecas, and finally, Mines and Massey (1985) in two communities in Zacatecas and Michoacán.…”
supporting
confidence: 85%
“…Reichert (1982) found a highly differentiated class structure in a community in Michoacán, where legal U.S. migrants occupied the highest economic ranks, followed by undocumented migrants and non-migrants. Mines (1981) and Mines and de Janvry (1982) reported wealth disparities in a community of Zacatecas, where committed U.S. migrants owned more land than either temporary migrants or non-migrants. Dinerman (1978) and Wiest (1973) observed a similar pattern of economic differentiation in Michoacán as did Cohen (2001) in Oaxaca.…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggested remittances may produce a cycle of dependency and stunted development in the origin (Papademetriou and Martin 1991;Reichart 1981;Wiest 1984) especially if the funds are spent on consumption rather than income-or employment-generating productive activities, hence contributing to a way of life that cannot be sustained in the long run or through local means (Brown and Alhburg 1999;Grasmuck and Pessar 1991;Massey and Basem 1992;Mills 1999;Mines 1982;Rempel and Lobdell 1978;Russell 1992). But recent work showed that remittances -even used for consumption -generate strong 'multiplier' effects in the receiving economy (Durand et al 1996a;.…”
Section: Introductionmentioning
confidence: 99%
“…Este fenómeno se explicaba, en algunos casos, por la pérdida de mano de obra agrícola (Massey, Goldring y Durand, 1994), por la falta de inversión de las remesas en la agricultura (Mines y De Janvry, 1982) o por la inversión de las remesas en la ganadería extensiva (García et al, 2009;Schmook y Radel, 2009). En cambio, en las comunidades estudiadas se comprobó que la migración no provocaba abandono de la agricultura campesina ni cambios sustanciales en ella.…”
Section: Discusión ¿La Migración Repercute En La Sustentabilidad De Lunclassified